2019
DOI: 10.1002/prot.25798
|View full text |Cite
|
Sign up to set email alerts
|

Ensembling multiple raw coevolutionary features with deep residual neural networks for contact‐map prediction in CASP13

Abstract: We report the results of residue‐residue contact prediction of a new pipeline built purely on the learning of coevolutionary features in the CASP13 experiment. For a query sequence, the pipeline starts with the collection of multiple sequence alignments (MSAs) from multiple genome and metagenome sequence databases using two complementary Hidden Markov Model (HMM)‐based searching tools. Three profile matrices, built on covariance, precision, and pseudolikelihood maximization respectively, are then created from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 41 publications
1
96
0
Order By: Relevance
“…C-I-TASSER improves our previously developed I-TASSER structure prediction protocol 26 by incorporating a deep-learning-based contact map prediction. 17,27 On all 121 CASP13 targets, the average TM score of the C-I-TASSER first model (0.674) is 8.0% higher than that of I-TASSER (0.624) and 0.15% higher than that of C-QUARK (0.673), which is our only other automated CASP13 server and was ranked in second place in CASP13.…”
Section: Relative Synonymous Codon Usage Analysismentioning
confidence: 95%
“…C-I-TASSER improves our previously developed I-TASSER structure prediction protocol 26 by incorporating a deep-learning-based contact map prediction. 17,27 On all 121 CASP13 targets, the average TM score of the C-I-TASSER first model (0.674) is 8.0% higher than that of I-TASSER (0.624) and 0.15% higher than that of C-QUARK (0.673), which is our only other automated CASP13 server and was ranked in second place in CASP13.…”
Section: Relative Synonymous Codon Usage Analysismentioning
confidence: 95%
“…The downside would be that the dilated filter will only be able to sample nine out of the 25 pixels and so will have “gaps.” However, these gaps can be filled by later dilated layers, so a network built with a mixture of dilated filters can cover an arbitrarily large receptive field without requiring an exponentially growing number of learnable parameters. In CASP13, dilated convolutions were used in a number of the top‐performing CNN models …”
Section: Convolutional Neural Network (Cnn) Modelsmentioning
confidence: 99%
“…In CASP13, dilated convolutions were used in a number of the top-performing CNN models. 7,41,42 Typical CNN models (eg, for image classification) take the output of one or more convolutional layers and usually downscale them with a "max pooling" operation. Max pooling simply looks for the maximum F I G U R E 1 A 2D convolutional filter (orange) is applied to an input layer (blue) to obtain the values for an output layer (green).…”
Section: Convolutional Neural Network (Cnn) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is exciting that information culled from sequences whose structures are not solved can serve as the primary input feature to predict contacts and distances. The most successful methods in the recent CASP13 experiment (http://predictioncenter.org/), a biannual protein structure and contact prediction competition, exploit such sequence databases and have unanimously demonstrated that a key to push the current progress is accurate contact and distance map prediction [2,3,4]. The distance prediction methods, in particular, are a major advancement in the area of ab initio or free modelling.…”
Section: Introductionmentioning
confidence: 99%